11 - Producing and Reproducing Inequality: Biopolitical Exclusion, Marginalized Bodies and AIDS Care in Central Mozambique - Braga, Carla Teófilo (Africa Development, 2017)
Studies of African countries’ response to HIV/AIDS and more recently to Ebola helped call into question not only individual and behavioural factors related to those conditions, but the centrality of the healthcare delivery systems themselves, particularly in the face of challenges of such magnitude. Weak, insufficient, underfunded and understaffed national health systems, compounded by international financial agencies’ discouragement, if not prevention, of increasing state budgets for social sectors, are usually considered the main challenges in assuring the population’s access to healthcare. In addition, and based on two years ethnographic fieldwork in central Mozambique (where in a neoliberal context, AIDS treatment is being provided through institutional arrangements comprising the state, aid agencies and international NGOs), this article suggests that access to healthcare and AIDS treatment, particularly by the poorest, can also be hindered by three factors. First, the adoption of a ‘one size fits all’ international AIDS treatment delivery model independent of context. Through the research of biomedical AIDS treatment services, this study brings to the fore the interplay of global health policies with the specificities of healthcare delivery at the local level, showing the importance of biomedical services’ organizational culture and history. Second, the production of institutionally stigmatizing categories to label non-adherent patients. As Ian Hacking pointed out categories have consequences for the ways we conceive of others, and those categorizations influenced the ways in which those patients were thought of, talked about and were dealt with within public health units. Third, the valorization of socio-economic markers of differentiation such as the tidiness and educational level of patients. Biomedical care is a complex social process performed within particular cultural matrices and laden with values. This study seeks to make visible the role played by the valorization, if not of a single and hegemonic conception of modernity, then at least of a ‘modern way of life’ (associated with the urban, hygiene and education) in access to AIDS treatment in central Mozambique.